The Oldest ‘Photography’, ‘The Abduction of Persephone’ - Bodó, Miháy (Eikón / Imago, 2021)
The essay focuses on The Abduction of Persephone, mural painting from Tomb I of Vergina, and is part of a larger investigation in which I have set out to analyze the pictorial structures of the few Greek works that have been preserved and have survived to this day. Through the reconstruction of the artistic creation processes, the article tries to reveal the knowledge of the craft of painting of the time. The results of the analysis show that it was the Hellenic workshops that laid the foundations for the visual communication tools that we use the most today, as well as the representation of form, light and shadow, space and even the use of linear perspective. The text is addressed both to specialists in the subject and to a wider audience. The graphic images produced by the author facilitate the understanding of the painting’s high pictorial level.